Diametral tensile strength and film thickness of an experimental dental luting agent derived from castor oil - Carmello, Juliana Cabrini [UNESP]; Grassi Fais, Laiza Maria [UNESP]; de Moraes Ribeiro, Ligia Nunes [UNESP]; Claro Neto, Salvador; Guaglianoni, Dalton Geraldo [UNESP]; Pereira Pinelli, Ligia Antunes [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2012)
The need to develop new dental luting agents in order to improve the success of treatments has greatly motivated research. Objective: The aim of this study was to evaluate the diametral tensile strength (DTS) and film thickness (FT) of an experimental dental luting agent derived from castor oil (COP) with or without addition of different quantities of filler (calcium carbonate - CaCO3). Material and Methods: Eighty specimens were manufactured (DTS N=40; FT N=40) and divided into 4 groups: Pure COP; COP 10%; COP 50% and zinc phosphate (control). The cements were mixed according to the manufacturers' recommendations and submitted to the tests. The DTS test was performed in the MTS 810 testing machine (10 KN, 0.5 mm/min). For FT test, the cements were sandwiched between two glass plates (2 cm(2)) and a load of 15 kg was applied vertically on the top of the specimen for 10 min. The data were analyzed by means of one-way ANOVA and Tukey's test (alpha=0.05). Results: The values of DTS (MPa) were: Pure COP- 10.94 +/- 1.30; COP 10%- 30.06 +/- 0.64; COP 50%- 29.87 +/- 0.27; zinc phosphate- 4.88 +/- 0.96. The values of FT (pm) were: Pure COP- 31.09 +/- 3.16; COP 10%- 17.05 +/- 4.83; COP 50%- 13.03 +/- 4.83; Zinc Phosphate- 20.00 +/- 0.12. One-way ANOVA showed statistically significant differences among the groups (DTS - p=1.01E-40; FT - p=2.4E-10). Conclusion: The experimental dental luting agent with 50% of filler showed the best diametral tensile strength and film thickness.
Keywords: Dental prosthesis; Biocompatible materials; Ricinus communis; Calcium carbonate; Zinc phosphate cement; Tensile strength